2016
DOI: 10.1111/bjd.15035
|View full text |Cite
|
Sign up to set email alerts
|

Is late-onset psoriasis a distinct subtype of chronic plaque psoriasis?

Abstract: Linked Article: Theodorakopoulou et al. Br J Dermatol 2016; 175:1038–1044.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, we found LOP was significant associated with anxiety and depression, but no significant correlation was observed in EOP. The explanation of our results may be that LOP patients were more commonly reported the symptoms of itching, sensitive skin, and burning and worry about the disease, which can result in psychological burdens (32). Moreover, LOP patients were common with chronic inflammatory comorbidities, such as type 2 diabetes, obesity, autoimmune thyroiditis, which can reduce the quality of life and increase the cost of treatment (33,34).…”
Section: Discussionmentioning
confidence: 87%
“…However, we found LOP was significant associated with anxiety and depression, but no significant correlation was observed in EOP. The explanation of our results may be that LOP patients were more commonly reported the symptoms of itching, sensitive skin, and burning and worry about the disease, which can result in psychological burdens (32). Moreover, LOP patients were common with chronic inflammatory comorbidities, such as type 2 diabetes, obesity, autoimmune thyroiditis, which can reduce the quality of life and increase the cost of treatment (33,34).…”
Section: Discussionmentioning
confidence: 87%
“…Finally, using a relatively low age cut-off (20 years old), a cross-sectional study reported that patients with EOP were significantly more anxious than those with LOP (83), although the reverse has been reported by other studies (76,78,82). Depression levels and their relationship to age of onset require further investigation as the results are conflicting (78,(82)(83)(84), which could be attributed to differences in the age cut-off levels and the use of different measures of depression (76). Also, the subjective perception of individuals about their condition and its impact might be different between EOP and LOP (85).…”
Section: Late-versus Early-onset Psoriatic Arthritis and Psoriasis Di...mentioning
confidence: 88%
“…People with LOP were less likely to be on treatment with biologics (78), which was even more noticeable in those with very late onset psoriasis (>70 years old) (81). Furthermore, post hoc analysis of data from four clinical trials of etanercept for psoriasis reported that treatment was more effective in patients with EOP compared to those with LOP (76,82). Finally, using a relatively low age cut-off (20 years old), a cross-sectional study reported that patients with EOP were significantly more anxious than those with LOP (83), although the reverse has been reported by other studies (76,78,82).…”
Section: Late-versus Early-onset Psoriatic Arthritis and Psoriasis Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early-onset psoriatic patients carriers of the HLA-Cw6 allele and late-onset psoriatic patients are characterized by clinical, demographic, immunocytochemical and genetic differences [53, 54]. Our results are incorporated in the above setting of the two distinct subtypes of psoriasis vulgaris [55].…”
Section: Discussionmentioning
confidence: 99%